Difficulties facing healthcare workers in the era of AIDS treatment in Lesotho - Masebeo Veronica Koto; Pranitha Maharaj (Taylor & Francis Group, 2016)
Sub-Saharan Africa is most affected by the AIDS pandemic and Lesotho is no exception. In many countries, healthcare workers are at the forefront of the fight against AIDS. This study explores the difficulties facing healthcare workers in Lesotho using a combination of qualitative methods - focus group discussions and in-depth interviews. The findings suggest that healthcare workers are afraid of contracting HIV from their patients and this affects their delivery of services. In addition, the results revealed that poor infrastructure and shortage of supplies at the facilities hinder healthcare workers from performing their duties effectively. The other concern was the heavy workload and severe time constraints which puts enormous stress on healthcare workers. Stigma and discrimination emerged as major problems for healthcare workers. Addressing the challenges facing healthcare workers is essential in effectively managing the AIDS pandemic facing the continent.